2002
DOI: 10.1016/s0896-6273(02)00746-8
|View full text |Cite
|
Sign up to set email alerts
|

Practice with Sleep Makes Perfect

Abstract: Improvement in motor skill performance is known to continue for at least 24 hr following training, yet the relative contributions of time spent awake and asleep are unknown. Here we provide evidence that a night of sleep results in a 20% increase in motor speed without loss of accuracy, while an equivalent period of time during wake provides no significant benefit. Furthermore, a significant correlation exists between the improved performance overnight and the amount of stage 2 NREM sleep, particularly late in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

38
435
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,117 publications
(501 citation statements)
references
References 25 publications
38
435
4
Order By: Relevance
“…However, there is, as yet, no firm evidence of an offline consolidation process for implicit sequence-specific learning. In contrast, this occurrence has been well documented for explicit sequence learning (Press et al, 2005;Walker et al, 2002). It may well be that whereas sleep is helpful towards the consolidation of explicit memory traces (i.e.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, there is, as yet, no firm evidence of an offline consolidation process for implicit sequence-specific learning. In contrast, this occurrence has been well documented for explicit sequence learning (Press et al, 2005;Walker et al, 2002). It may well be that whereas sleep is helpful towards the consolidation of explicit memory traces (i.e.…”
Section: Introductionmentioning
confidence: 93%
“…Evidence of offline motor memory consolidation in conjunction with explicit sequence learning was found when participants performed a finger-tapping task with two training sessions (Doyon et al, 2009;Walker, Brakefield, Morgan, Hobson, & Stickgold, 2002;Walker, Brakefield, Seidman, et al, 2003). Specifically, after one night's sleep, with no further practice between sessions, participants showed marked improvements in speed and accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for robust delayed gains in performance that emerged after a latent period of more than a few hours after a single-session training, the notion of an intermediate phase corresponding to the posttraining hours has been proposed (2, 7, 13, 27-31). The conjecture is that a process of memory consolidation requiring time to become effective (in terms of performance) can be triggered by the training experience under certain conditions and requires time to become effective (in terms of performance) in both perceptual and motor tasks [but also in the acquisition of cognitive skills (12)].Recent studies further suggest that sleep may contribute significantly to the development of the delayed gains in this type of learning (28,30,32).It is not clear, however, whether the effects of a single training session, with ample time given for the evolution of delayed gains, can be conceptualized as the unit of skill acquisition, i.e., that multisession training gain constitutes but the sum of incremental gains of a number of single sessions. An earlier study (2) showed that all gains in speed of performance after completing longterm training on a sequence of movements were highly restricted by the physical parameters of the training experience, with no transfer to the untrained hand or to different arrangements of the trained movement components comprising the sequence.…”
mentioning
confidence: 99%
“…Such replay of experience-dependent activity during sleep have already been reported in rat hippocampus after training on spatial learning tasks (21,22) and in human cortex after training on an implicit motor sequence task (23). Improvement on both spatial learning tasks and simple motor sequence tasks has been shown at the behavioral level to be at least partially sleep dependent (24,25). Additional brain-based evidence for slow, experience-dependent changes in cortical activity comes from other studies.…”
mentioning
confidence: 64%